Clinical Practice Survey of Repeat Endoscopy in Pediatric Inflammatory Bowel Disease in North America. Issue 1 (July 2021) - Moses, Jonathan; Sandberg, Kelly; Winberry, Gabriel; Riera, Diana; DeLozier, Sarah; Gupta, Sandeep K.; Reilly, Norelle; Park, KT; Picoraro, Joseph
ABSTRACT: Objectives: Endoscopic remission has become a standard treatment target in inflammatory bowel disease (IBD). It is unclear how widely this practice has been adopted amongst pediatric gastroenterology providers. This study determines the frequency of repeat endoscopy in pediatric IBD and evaluates for predictive baseline characteristics of providers. Methods: We developed a cross-sectional survey, which was distributed via 3 national email listservs to pediatric gastroenterology providers. We obtained baseline characteristics of respondents and assessed motivations and barriers for the practice of repeat endoscopy compared with none. Results: Two hundred and thirty-eight unique respondents completed the online survey. Response rate was 11% (238 of 2300 possible participants). The majority practice in an academic setting (77%) and reported participation in ImproveCareNow (63%). Overall, 65% of respondents perform repeat endoscopy to assess for endoscopic remission in pediatric IBD as part of routine clinical practice. Fifty-six percent reported repeat endoscopy as individuals in the absence of a departmental protocol. "Symptoms are not sufficient to follow IBD patients" was reported by 82% of those who repeat endoscopy; conversely, "I perform endoscopy based on clinical, biomarker, and/or imaging trends" was reported by 81% of those who do not repeat endoscopy. The establishment of a pediatric-specific guideline was most commonly reported to change current practice, based on rank-order scoring. Conclusions: A majority of representative providers repeat endoscopy to assess for endoscopic remission in pediatric IBD. Fewer years in practice favored repeating endoscopy. The need for North American pediatric guidelines with pediatric-specific evidence to support the long-term benefits of endoscopic remission are highlighted in this study.